PENGARUH PENGEMBANGAN KARIR DAN KONFLIK TERHADAP PRODUKTIFITAS KERJA PADA BADAN PENGELOLA KEUANGAN, PENDAPATAN DAN ASET DAERAH KABUPATEN KARO - Dearma Sariani Sinaga; Julhendri Sinaga; Frisderesia Sinaga (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The purpose of the research is to see if “The Career-Influence Development and Conflict Effect The Work Productivity in Financial Management Revenue and Expenditure Asset of Karo Regency." The sample in this study is 41 people ". Data collection techniques using questionnaires. From the results of the linear regression multiple test that a partial value is known to be count x1 (7.780 > T.table = 1.682 meaning there is a career-development influence on work productivity. Count x2 (3.462) > T.table = 1,682 meaning there is the impact of conflict on work productivity. There are simultaneously significant effects of career development and conflict on career development. This is proved that partial testing (test-f) is known by Fcount > Ftable and sig-p value 0.05. Adjusted R square value: 0.782 means that the overall impact of career development and conflict of the work productivity is 78.2%. The most influential variable in occupational productivity is career development of 67%. The conclusion of this research is that there is a career-development effect on work productivity, there is a conflict on work productivity, and there is a career-development and conflict on work productivity